2012
DOI: 10.1177/1753193412445162
|View full text |Cite
|
Sign up to set email alerts
|

The results of carpal tunnel release for carpal tunnel syndrome diagnosed on clinical grounds, with or without electrophysiological investigations: a randomized study

Abstract: We compared the results of carpal tunnel release in patients with the diagnosis of carpal tunnel syndrome based on only clinical grounds and those diagnosed on clinical and electrophysiological grounds. Ninety-three patients, 83 women (89%) and ten men (11%), meeting the criteria of 'typical' carpal tunnel syndrome, were randomly assigned to receive carpal tunnel release with (n = 45, 48%) or without (n = 48, 52%) nerve conduction studies. Patients were followed-up at 1 and 6 months, by assessments that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
1
22
1
2
Order By: Relevance
“…The results of our study based on the relatively large number of patients operated on for CTS show that there is no difference in post-surgical outcomes whether patients are diagnosed clinically without-or diagnosed clinically with electrodiagnostic studies, so, therefore, electrodiagnostic studies can be omitted from patients presenting with classic CTS. This conclusion is consistent with the results of our earlier prospective and randomised (but smaller) study [8]. Single similar studies have been performed in the last 20 years, such as that of Finsen and Russwurm (2001), who reported outcomes of surgical treatment in 68 patients with classical CTS, who underwent electrophysiological investigation preoperatively, but the results of these were not assessed until the end of the study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of our study based on the relatively large number of patients operated on for CTS show that there is no difference in post-surgical outcomes whether patients are diagnosed clinically without-or diagnosed clinically with electrodiagnostic studies, so, therefore, electrodiagnostic studies can be omitted from patients presenting with classic CTS. This conclusion is consistent with the results of our earlier prospective and randomised (but smaller) study [8]. Single similar studies have been performed in the last 20 years, such as that of Finsen and Russwurm (2001), who reported outcomes of surgical treatment in 68 patients with classical CTS, who underwent electrophysiological investigation preoperatively, but the results of these were not assessed until the end of the study.…”
Section: Discussionsupporting
confidence: 90%
“…Accurate diagnosis without nerve conduction studies (NCS) could result in reduction of delays in treatment, which might improve the efficiency and overall quality of patient care. Some studies have shown that performing nerve conduction studies did not improve the outcomes of surgery for carpal tunnel syndrome [5][6][7][8]. The objective of this study was comparison of the results of carpal tunnel release in patients diagnosed with and without electrophysiological studies in order to confirm or reject the hypothesis that preoperative electrophysiological testing adds valuable information for improving outcomes of surgery.…”
Section: Introductionmentioning
confidence: 96%
“…Measurements from each finger were added and then divided by 3, which gave the final sensory index. 13 Grip strength and key pinch were measured using a Jamar dynamometer and a pinch gauge (Asimow Engineering, Los Angeles, CA) with the elbow flexed at 90 and the forearm in neutral rotation. Assessment of symptoms and the functional state of patients was achieved prospectively based on the Boston Carpal Tunnel Questionnaire (BCTQ).…”
Section: Methodsmentioning
confidence: 99%
“…Én av grunnene er dårlig kvalitet på mange vitenskapelige studier (2). I en studie som Russwurm & Finsen fremhever (1), sammenlikner man tilsynelatende effekten av nevrografi og det postoperative resultatet (5). Ved å lese artikkelen fremgår det imidlertid at nevrografiresultatet verken ble brukt i diagnostikken eller i dataanalysen.…”
Section: Per Sundbyunclassified